(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The analysis of the role of Third sector in the palliative care system starts from the concept of social-health integration. Palliative medicine develops an integrated assistance, where “care” and “taking care” are not aimed at healing, but at reducing the physical and mental suffering of the person, favored by the care work of the Third sector. The focus of this paper is to highlight how in the sphere of palliative care networks the contribution of the voluntary organizations is a condition for implementing an efficient system of social and health integration, also as a response to the Covid emergency.